ANALISIS BENEISH M-SCORE DALAM MENDETEKSI INDIKASI FRAUD LAPORAN KEUANGAN - Anggraeni, Fitri Nur; Tarjo (APSSAI, 2024)
This research aims to detect indications of fraud in a financial report using the Beneish M-Score. PT TIMAH Tbk is a mining sector company used as the object of this research. This type of research is a case study with a descriptive approach. The kind of data used is secondary data in the form of the annual financial report of PT TIMAH Tbk for 2018 - 2022. The data collection method uses literature study and documentation methods to obtain the required data. The data analysis technique uses the Beneish M-Score Model with index ratio analysis techniques. The research results show that in 2018 and 2019, PT TIMAH Tbk was classified as a manipulator company, while in 2020, 2021, and 2022, it was classified as a non-manipulator company. At PT TIMAH Tbk, all the DSRI, GMI, AQI, SGI, DEPI, SGAI, LVGI, and TATA ratios prove that there are indications of financial report fraud, so these ratios can be used as a tool to detect fraud in PT TIMAH Tbk's financial reports.